How Volunteer Commitment Differs in Online and Offline Environments. (November 2022) - Ihm, Jennifer; Shumate, Michelle
The contemporary media environment transforms the organization-volunteer relationship by attenuating the formation of organizational belonging, often thought to be the result of direct interactions and face-to-face meetings. We examine and compare factors that influence offline and online volunteering. We investigate the ties for communicating about volunteering that bind individuals to nonprofit organizations (NPOs) and the ways that multiple levels of identification influence volunteer commitment to these NPOs. Using structural equation modeling, the results from an online survey of 816 volunteers suggest that online volunteers, unlike offline volunteers, are not motivated to volunteer more by exclusive relationships with organizational members or their volunteer identity. Their volunteering is related to their communication ties with both members and nonmembers and their identification with both the organization and the social issue. We discuss implications regarding how the changed dynamics in online volunteering complicates the traditional organization-volunteer relationship.